2023
DOI: 10.1128/jvi.01227-22
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of African Swine Fever Virus (ASFV) H240R Gene Attenuates the Virulence of ASFV by Enhancing NLRP3-Mediated Inflammatory Responses

Abstract: African swine fever (ASF), caused by African swine fever virus (ASFV), is a highly contagious and acute hemorrhagic viral disease of domestic pigs, with a high mortality approaching 100%. ASFV has spread rapidly worldwide and caused huge economic losses and ecological consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
1
17
2
Order By: Relevance
“…Notably, MGF300-4L is among several ASFV proteins including, H240R, MGF505-7R, and MGF300-2R, all of which inhibit NF- κ B activation. When deleted individually from ASFV, they cause an attenuation phenotype in vivo [ 13 , 26 , 27 ]. Intuitively, it seems unlikely that the attenuation would occur due to the loss of a single NF- κ B inhibitor, especially when other inhibitors are still present.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, MGF300-4L is among several ASFV proteins including, H240R, MGF505-7R, and MGF300-2R, all of which inhibit NF- κ B activation. When deleted individually from ASFV, they cause an attenuation phenotype in vivo [ 13 , 26 , 27 ]. Intuitively, it seems unlikely that the attenuation would occur due to the loss of a single NF- κ B inhibitor, especially when other inhibitors are still present.…”
Section: Discussionmentioning
confidence: 99%
“…After deleting these genes individually from highly virulent ASFV strains, a significant decrease in pathogenicity and virulence can be observed in the mutants ( Table 2 ). Previous studies have confirmed that deletion of the H240R gene will enhance NLRP3-mediated inflammatory responses, resulting in the attenuation of ASFV [ 112 ]. Of note, MGF505-7R has proven to be a multifunctional protein, playing crucial roles in suppressing cGAS-STING-mediated IFN-I production, IFN-II-induced antiviral response, and NLRP3 inflammasome activation [ 65 ].…”
Section: Effects Of Immune Evasion On Viral Replication and Virulencementioning
confidence: 96%
“…ASFV pH240R serves as a robust suppressor of IL-1β transcription, maturation, and secretion, along with restraining NLRP3 inflammasome activation in inflammatory responses ( Huang et al , 2023 ). Its inhibitory actions extend beyond NF-κB signaling to encompass NLRP3 inflammasome activation.…”
Section: Introductionmentioning
confidence: 99%
“…These findings underscore the pivotal role of pH240R in ASFV virulence, indicating its potential as a subject for in-depth exploration into ASFV immune evasion mechanisms. Such investigations may pave the way for the development of attenuated live vaccines and therapeutic interventions for effective ASF prevention and control ( Huang et al , 2023 ).…”
Section: Introductionmentioning
confidence: 99%